The role of brand engagement in self-concept toward brand love and brand advocacy - Pram Suryanadi; Aldwin Marciadi (Universitas Sebelas Maret, 2020)
This research examines the impact of relevance between brand engagement in self-concept, brand love, and confidence toward brand advocacy and moderation by involvement and subjective knowledge. The population of this research is a generation of millennials in Indonesia with an age range of 18 to 28 who have purchased and used Converse shoes with a minimum of 6 (six) months. Research samples were taken 220 respondents with purposive sampling techniques and primary data obtained from online questionnaires using LimeSurvey's website. The data obtained is tested using Smart PLS 3.2.8 software. The results show that brand engagement in self-concept and brand love positively affects brand advocacy; brand love positively affects brand engagement in self-concept, and confidence positively affects brand love.